EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK TERHADAP KEMAMPAUAN PEMECAHAN MASALAH MATEMATIS SISWA - Syahru Romadhon; Yulia Pratiwi Siregar (JURNAL MathEdu (Mathematic Education Journal), 2019)
The aim of this study is to know whether there is the effectiveness of using talking stick learning model on students’ mathematical problem solving ability on the topic of system of two variable equations at the eighth grade students of MTs Swasta AL-Aminatul Hidriyah Pangirkiran. This research was conducted by applying experimental (one group pre test post test design) with 39 students as the sample and they were taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using talking stick learning model was 3.46 (very good category) and (b) the average of students’ mathematical problem solving ability on the topic of system of two variable equations before using talking stick learning model 59.69 (fair category) and after using talking stick learning model was 79.12 (good category). Furthermore, by using pair sample ttest and help SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, using talking stick learning model was effective used on students’ mathematical problem solving ability on the topic of system of two variable equations at the eighth grade students of MTs Swasta AL-Aminatul Hidriyah Pangirkiran.